The heart of Islam - Blanton, Stephen (AuthorHouse, 2011)
What motivates some followers of Islam to commit terrorist acts? What does the Islamic holy book say about murder, war, and women's rights? Why won't moderate Muslims speak out against mass murder committed by their extremist brothers? Should we take Islamic jihadists seriously when they proclaim their goal of world conquest? Can anything be done to stop Islamic violence? The Heart of Islam answers these questions clearly and succinctly with easily verifiable facts. The world view of Islam will change when its doctrines, strategies and history become widely known. The time to learn is now--Publisher's description.